Mendelian randomization analysis demonstrates the causal effects of IGF family members in diabetes - Li, Xing; Tang, Jie; Lin, Sha; Liu, Xuwei; Li, Yifei (Frontiers in Medicine, 2024)
Background: Observational studies have consistently shown significant associations between the IGF family and metabolic diseases, including diabetes. However, these associations can be influenced by confounding factors and reverse causation. This study aimed to assess the causal relationship between the IGF family and diabetes using Mendelian randomization (MR). Methods: We conducted a two-sample MR analysis to investigate the causal effects of the IGF family on diabetes. Instrumental variables for the IGF family and diabetes were derived from summary-level statistics obtained from genome-wide association studies. Horizontal pleiotropy was assessed using MR-Egger regression and the weighted median method. We applied the inverse-variance weighted method as part of the conventional MR analysis to evaluate the causal impact of the IGF family on diabetes risk. To test the robustness of the results, we also employed MR-Egger regression, the weighted median method, and a leave-one-out analysis. Results: Our study revealed that IGF-1 causally increases the risk of Type 2 Diabetes (T2D), while IGFBP-6, adiponectin and INSR decreases the risk (IGF-1, OR 1.02 [95% CI 1-1.03], P=0.01; IGFBP-6, OR 0.92 [95% CI 0.87-0.98], P=0.01; Adiponectin, OR 0.837 [95% CI 0.721-0.970], P=0.018; INSR, OR 0.910 [95% CI 0.872-0.950], P=1.52×10-5). Additionally, genetically lower levels of IGF-1 and IGFBP-5, along with higher levels of IGFBP-7, were associated with an increased risk of Type 1 Diabetes (T1D) (IGF-1, OR 0.981 [95% CI 0.963-0.999], P=0.037; IGFBP-5, OR 0.882 [95% CI 0.778-0.999], P=0.049; IGFBP-7, OR 1.103 [95% CI 1.008-1.206], P=0.033). Conclusion: In summary, our investigation has unveiled causal relationships between specific IGF family members and T1D and T2D through MR analysis. Generally, the IGF family appears to reduce the risk of T1D, but it presents a more complex and controversial role in the context of T2D. These findings provide compelling evidence that T2D is intricately linked with developmental impairment. Our study results offer fresh insights into the pathogenesis and the significance of serum IGF family member concentrations in assessing diabetes risk.